Analisis Faktor-faktor yang Mempengaruhi Produksi Padi Sawah pada Daerah Tengah dan Hilir Aliran Sungai Ayung (Studi Kasus Subak Mambal, Kabupaten Badung dan Subak Pagutan, Kota Denpasar) - ADE CANDRA PRABANDARI; MADE SUDARMA; PUTU UDAYANI WIJAYANTI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2013)
ABSTRACT Analysis of The Factor Affecting Rice Production in The Central Region and The Downstream Flow of The ayung River (Case Study in Subak Mambal, Badung Regency and Subak Pagutan, City of Denpasar). Subak Mambal and Subak Pagutan are using the river Ayung as irrigated rice fields. Subak Mambal in Badung Regency is located at middlestream and Subak Pagutan in Denpasar city is located at downstream of Ayung river . The Purpose of this study are to determine of the factors that influence the rice production at both of Subak, knowing the different of rice production at both of Subak , and determine of irrigation constraints for paddy rice at both of Subak. This research was done by interview 50 respondents in the two Subak. Based on analysis of linear regression showed three variables which are influence on rice production, employee, fertilizer and water, while the other variables are not affected. Analysisi of difference of production between in two subak, showed there is significant different between rice productioan at Subak Mambal and Subak Pagutan, where rice production at Subak Mambal higher than Subak Pagutan. The contraints of water irrigation at Subak Mambal is clogged of irrigation canals due to the garbage, and for Subak Pagutan are: (1) the damage of system irrigation, (2) pest crab, (3) garbage, (4) silting of rivers. Keyword : rice, production, constarain